2018
DOI: 10.1177/0018720818759102
|View full text |Cite
|
Sign up to set email alerts
|

What You Don’t Notice Can Harm You: Age-Related Differences in Detecting Concurrent Visual, Auditory, and Tactile Cues

Abstract: Objective This research sought to determine whether people can perceive and process three nonredundant (and unrelated) signals in vision, hearing, and touch at the same time and how aging and concurrent task demands affect this ability. Background Multimodal displays have been shown to improve multitasking and attention management; however, their potential limitations are not well understood. The majority of studies on multimodal information presentation have focused on the processing of only two concurrent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 50 publications
(57 reference statements)
6
15
0
Order By: Relevance
“…Furthermore, we expected higher multitask costs in the quadruple condition compared to the dual condition, in line with research showing a detrimental effect on multitask costs of having to process more than two tasks (e.g. Doumas and Krampe 2013;Bock et al 2018;Pitts and Sarter 2018;Devesse et al 2019).…”
Section: Introductionsupporting
confidence: 86%
“…Furthermore, we expected higher multitask costs in the quadruple condition compared to the dual condition, in line with research showing a detrimental effect on multitask costs of having to process more than two tasks (e.g. Doumas and Krampe 2013;Bock et al 2018;Pitts and Sarter 2018;Devesse et al 2019).…”
Section: Introductionsupporting
confidence: 86%
“…However, multitasking in real-life often involves the processing of more than two tasks and it has been shown before that the processing of more than two simultaneous cues may negatively influence performance on an alternate task. For example, Pitts and Sarter (2018) showed that performance on a driving task was impaired for both young and old participants when they simultaneously had to detect more than two nonredundant cues in different sensory modalities. Also, Doumas & Krampe (2013) found higher dual-task costs in a triple-task condition compared to a dual-task, when combining a working memory task together with a finger force and/or postural control task.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in manual driving, Lundqvist and Eriksson (2019) and Politis, Brewster, and Pollick (2014), evaluated all uni-, bi-, and trimodal combinations of visual (V), auditory (A), and tactile (T) cues (i.e., V, A, T, VA, VT, AT, and VAT) and showed multisensory performance gains, in terms of response times to signals. Pitts and Sarter (2018) confirmed these benefits, even though they explained that their 7 stimuli were partially redundant. Still, to date, very few studies have investigated the extent to which these findings generalize to the context of autonomous driving, where the attention allocation of a driver disengaged from the driving task may be very different from that of a manual driver.…”
Section: Introductionmentioning
confidence: 89%
“…Tactile signals were created using two C-2 tactors, which are 1" × 0.5" × 0.25" piezo-buzzers (developed by Engineering Acoustics, Inc.) with frequency of 250 Hz. The two tactors were attached to a belt and positioned across the lower back (as inPitts & Sarter, 2018). When activated, both tactors vibrated at the same time.Driving Environment: Road Signs.…”
mentioning
confidence: 99%